Woman, Life, Freedom : On protests in Iran and Why it is a feminist movement - Mehrabi, Tara (Kvinder, Køn & Forskning, 2023)
In this essay, I draw on the lyrics of a viral song by Shervin Hajipour titled “Baraye” (meaning: for the sake of) that was released on 28 September 2022 and immediately became the anthem of the protests in Iran. I quote excerpts of the lyrics in three sections of this essay, connecting them to the slogan “Woman, Life, Freedom” chanted in the streets and the symbolic act of cutting one’s hair that has come to represent the protests. In the first of these sections, on woman, I reflect on the regime’s gender politics (of hair), arguing that the act of cutting one’s hair becomes a symbolic act of resisting such gender politics. In the second section, on life, I focus on the act of cutting hair as a mode of mourning the unjust and untimely deaths, for which accountability is demanded. In the last section, on freedom, I focus on the sexual politics of hair and the politics of the veil. I argue that cutting one’s hair is a symbolic act of resisting modes of sexualization that are used by the regime to justify mandatory hijab. Putting together the three parts – woman, life, freedom – I conclude that cutting one’s hair is a feminist act of resistance, an exercise of agency through which Iranian women are taking control and reclaiming their womanhood, their lives, their bodies and their freedom of choice.